Characterizing the Switching Thresholds of Magnetophoretic Transistors. (9th September 2015) - Abedini‐Nassab, Roozbeh; Joh, Daniel Y.; Van Heest, Melissa A.; Yi, John S.; Baker, Cody; Taherifard, Zohreh; Margolis, David M.; Garcia, J. Victor; Chilkoti, Ashutosh; Murdoch, David M.; Yellen, Benjamin B.
<x xml:space="preserve">Abstract</x> The switching thresholds of magnetophoretic transistors for sorting cells in microfluidic environments are characterized. The transistor operating conditions require short 20–30 mA pulses of electrical current. By demonstrating both attractive and repulsive transistor modes, a single transistor architecture is used to implement the full write cycle for importing and exporting single cells in specified array sites.